(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
Background: Febrile seizure-(FS) remains the commonest benign convulsive childhood event. Prolonged-FS may have long-term consequences, including increased risk of subsequent-epilepsy. Objective: To assess if there is any association among epilepsy and epilepsy syndrome with FS. Methodology: This cross-sectional study was conducted in Epilepsy Clinic, National Institute of Neurosciences, Bangladesh, from January-June, 2021 involving one hundred 1-18 years-old-children diagnosed as epilepsy without secondary causes (intracranial space occupying lesion, head-trauma, CNS-infection, stroke). Patients were clinically evaluated thoroughly and were divided into two groups (Gp): Gp-A having a history of (H/O) FS and Gp-B, without FS. Demographically, clinical profile and electrophysiological-parameters were compared between the two groups for association with H/O FS. Pre-checked/cleaned-data were analyzed using SPSS.V.22.0 for proportional differences, taken p<.05 as significant (95%-CI). It was distributed nearly equally among both sexes, irrespective of FS. Although generalized epilepsy was common in both 12/14 (85.71%) Gp-A Vs. 54/86 (62.79%) Gp-B; epilepsy syndrome (infantile spasm, LGS, JME, JAE) revealed significantly more among non-FS-children than genetic epilepsy FS+ was more in FS group (p = 0.04). On EEG, generalized slowing [2/14 (14.28%)], generalized discharge [3/14 (21.42%) and features of encephalopathy [3/14 (21.42)] was observed more in patients with H/O FS, than non-FS. Conclusion: In contrast to other types of epilepsy, our study revealed that genetic epilepsy febrile seizures + was associated with epileptic children who had H/O FS. The Journal of Ad-din Women’s Medical College; Vol. 11 (1), Jan 2023; p 38-43